2016
DOI: 10.1177/1479164115611594
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 promotes mesenchymal stem cell revascularization of limb ischaemia

Abstract: This study examines the effect and mechanism of action of Netrin-1 on bone marrow mesenchymal stem cells in angiogenesis. Tube formation and migration of bone marrow mesenchymal stem cells were observed in cell culture. Bone marrow mesenchymal stem cells or Netrin-1-bone marrow mesenchymal stem cells were injected into the ischaemic area of the rat hind limb on the first day after surgery. Laser Doppler perfusion imaging was performed to analyse the levels of vascular endothelial growth factor in plasma and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The Netrin protein family, which acts in the nervous system in axonal guidance [ 3 ], has later been found to be implicated in angiogenesis [ 37 ], cell survival [ 38 ], and morphogenesis [ 39 ]. Moreover, recent studies suggest that Netrin-1 may become a therapeutic target in the treatment of various pathologies, either as a stimulant or inhibitor of angiogenesis such as in diabetes or cancer, respectively, even protecting the heart against ischemia-reperfusion injury [ 2 , 40 , 41 ]. However, the underlying cellular mechanisms and receptor specificity characteristics involved in angiogenesis still require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Netrin protein family, which acts in the nervous system in axonal guidance [ 3 ], has later been found to be implicated in angiogenesis [ 37 ], cell survival [ 38 ], and morphogenesis [ 39 ]. Moreover, recent studies suggest that Netrin-1 may become a therapeutic target in the treatment of various pathologies, either as a stimulant or inhibitor of angiogenesis such as in diabetes or cancer, respectively, even protecting the heart against ischemia-reperfusion injury [ 2 , 40 , 41 ]. However, the underlying cellular mechanisms and receptor specificity characteristics involved in angiogenesis still require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ke et al studied the positive effect of Netrin-1 on BMSCs in proliferation, migration, tube formation, and promotion in revascularization of rat limb ischemia. The study measured the plasma and tissue levels of VEGF and confirmed the upregulation of VEGF as the leading cause of the positive effect of Netrin-1-carrying BMSCs in the revascularization of rat limb ischemia [ 33 ].…”
Section: Discussionmentioning
confidence: 98%
“…Fan et al demonstrated that netrin-1 induced blood vessel formation in the brain of adult mice and ameliorated cerebrovascular development and remodeling [ 52 ]. Other studies have reported that netrin-1 accelerated revascularization and reperfusion in mice suffering from hindlimb ischemia [ 20 , 53 ], and that netrin-1 augmented the angiogenesis of mesenchymal stem cells and improved the function of the ischemic hindlimb [ 51 ]. Also, netrin-1 is found to be superior to vascular endothelial growth factor in restoring nerve conduction velocity, possibly due to its strong biological effects on both the nervous and vascular system [ 20 ].…”
Section: Discussionmentioning
confidence: 99%